ANALYSIS OF GO LABA MUSICAL ELEMENT OF NGADA TRADITIONAL MUSIC AS THE ACCOMPANIMENT OF JA’I DANCE IN MORA MASA STUDIO TUAK DAUN MERAH (TDM 02) SUB-SUB DISTRICT OEBOBO DISTRICT - KUPANG - Flora Ceunfin; Melkior Kian; Maria Klara Amarilis Citra Sinta Dewi Tukan (LPPMPP Institut Seni Indonesia Padangpanjang, 2019)
Go Laba is the traditional musical instrument of Ngada found in the studio of Mora Masa, Kupang city Nusa Tenggara Timur. Its playing pattern emphasizes more on the repetitions of rhythm. In this article, it's discussed (1) the presentation form of Go Laba as the accompaniment pattern of Ja'l dance in Mora Masa studio, Tuak Daun Merah village, Oebobo sub-district; (2) the musical element of Go Laba as the accompaniment pattern of Ja'l dance in Mora Masa studio, Tuak Daun Merah village, Oebobo sub-district. The traditional music of Go Laba consists of five gongs namely Go Wela, Go Ute, Go Dhere, Go Doa, Laba Wai and Laba Dhera. The presentation of Go Laba is the intertwined playing of rhythm that emphasizes more on the repetition of sound in order to create an aesthetic impression with 2/4 birama. Go Laba in its playing uses allegro tempo found in the rhythm of Go Wela. Based on research results, it can be concluded that Go Laba found in Mora Masa studio functions as the accompaniment of Ja'l dance used for the necessity in entertainment event and participating in the dance festival.